Tiktokshop’s Acquisition of Tokopedia in Providing Justice for Micro, Small and Medium Enterprises (Study: Tiktokshop E-Commerce Services in Indonesia) - Dylan Rajasa Chandra; Sugiyono, Heru (Dinasti Research, 2024)
The purpose of this study is a study of the protection of law and justice that exists in Indonesia related to the occurrence of actions by a number of Micro, Small and Medium Enterprises actors on the decision to acquire Tokopedia made by Bytedance as the parent of Tiktokshop. This research was conducted using the normative juridical method because it is based on legal norms in legislation and legal principles. The results of this study indicate that the partnership between Tiktokshop and Tokopedia provides problems of justice for business actors where one party benefits from Tiktokshop's innovation and the other party feels disadvantaged because of gaps in business competition. With the existence of laws that regulate legal protection for Micro, Small and Medium Enterprises, especially with the enactment of Regulation of the Minister of Trade Number 31 of 2023 concerning Business Licensing, Advertising, Guidance and Supervision of Business Actors in Trading through Electronic Systems, it can be said that existing regulations if implemented can provide benefits to business actors in providing justice and legal protection for Micro, Small and Medium Enterprises.